2018
DOI: 10.1177/1073191118818754
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Merrill–Palmer–Revised Scales of Development in Preschool Children With Autism Spectrum Disorder

Abstract: Psychometrically sound tests of intellectual ability are indispensable for research and assessment of children with autism spectrum disorder (ASD), yet few tests have been validated for use with this population. The Merrill–Palmer–Revised Scales of Development (M-P-R) is a standardized test of intellectual ability that was validated for use with typically developing preschoolers. The current study’s aim was to investigate the criterion validity of the M-P-R for assessing cognitive skills in preschoolers with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Scores across the three subscales are combined to produce a summary score, the Developmental Index (DI; M = 100, SD = 15). In a sample of 180 preschool-aged autistic children, Dempsey et al (2020) found evidence of good concurrent and predictive validity of the MPR with other wellvalidated measures of cognition and receptive language.…”
Section: Merrill-palmer-revised Scales Of Development (Mpr)mentioning
confidence: 94%
“…Scores across the three subscales are combined to produce a summary score, the Developmental Index (DI; M = 100, SD = 15). In a sample of 180 preschool-aged autistic children, Dempsey et al (2020) found evidence of good concurrent and predictive validity of the MPR with other wellvalidated measures of cognition and receptive language.…”
Section: Merrill-palmer-revised Scales Of Development (Mpr)mentioning
confidence: 94%
“…(Roid & Sampers, 2004 ) is a standardized measure of intellectual ability for children between 2 and 78 months old. The Developmental Index age equivalent score was used; this score comprises Cognitive, Receptive Language, and Fine Motor indices (Dempsey et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The M-P-R is a standardized measure that is ideal for screening infants and children for early identification of developmental delays and learning difficulties. The measure has been validated for use in children diagnosed with autism and has demonstrated good concurrent validity (Dempsey et al, 2018) with other standardized cognitive (Wechsler Intelligence Scale; 5th ed.) and language (Preschool Language Scale–4th ed.)…”
Section: Methodsmentioning
confidence: 99%